2005
DOI: 10.1055/s-2004-830334
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intensity and Duration Affect Blood Soluble HSP72

Abstract: Soluble heat shock protein 72 (sHSP72) is suggested to play a role as a signalling molecule in the immune response to exercise. We were interested in whether duration and intensity of endurance running affect the level of inducible sHSP72 in the plasma/serum of endurance athletes. In the first part of the study, the influence of a continuous treadmill run of 60 min (CR) with an intensity of 75 % VO2max, a long treadmill run of 120 min (LR) with an intensity of 60 % VO2max, an extensive interval training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 75 publications
(53 reference statements)
10
80
2
Order By: Relevance
“…Released from hepatosplanchnic tissues (20) in an intensity-and durationdependent manner (24,45), eHSP72 can induce LPS tolerance in THP-1 cells (2) and has been related to the inflammatory status during heat illness (51,61). We observed a greater eHSP response in TR compared with UT subjects, similar to the intracellular differences and findings reported by others (60).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Released from hepatosplanchnic tissues (20) in an intensity-and durationdependent manner (24,45), eHSP72 can induce LPS tolerance in THP-1 cells (2) and has been related to the inflammatory status during heat illness (51,61). We observed a greater eHSP response in TR compared with UT subjects, similar to the intracellular differences and findings reported by others (60).…”
Section: Discussionsupporting
confidence: 81%
“…Circulating levels of eHSP72 have been suggested to play an important systemic role, acting as an extracellular danger signal to activate immune responses (24,33). Released from hepatosplanchnic tissues (20) in an intensity-and durationdependent manner (24,45), eHSP72 can induce LPS tolerance in THP-1 cells (2) and has been related to the inflammatory status during heat illness (51,61).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we did not observe a difference in circulating eHsp72 concentration between EIMD trials. It is noteworthy however, that the circulating IL-6 and eHsp72 responses prior to HS during EIMD trial 1 were modest when compared with more metabolically challenging activities such as marathon running (Fehrenbach et al 2005;Nieman et al 2001), and therefore provided little margin for dampened responses.…”
Section: Discussionmentioning
confidence: 98%
“…First, the time of return to baseline value for salivary eHSP70 levels is still unclear. Previous studies showed that circulating eHSP70 increased temporarily (Fehrenbach et al 2005;Whitham et al 2006) and returned to baseline within 8 or 24 h, after intense exercise (Walsh et al 2001;Suzuki et al 2006). Although the reaction times to respond to exercise stress in circulating eHSP70 and salivary eHSP70 were different, it was assumed that exercise-induced salivary eHSP70 levels might return to baseline within 24 h. Changes in eHSP70 levels should be observed for more than 4 h or until 1 or 2 days after exercise to completely determine the changes in levels at various times until return to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…iHSP70 levels increase in response to exercise-induced stressors such as heat, reactive oxygen species (ROS), and hypoxia in cells (Fehrenbach and Northoff 2001). Actually, a single bout of exercise increases circulating eHSP70 level (Walsh et al 2001;Febbraio et al 2002;Fehrenbach et al 2005) and heat stress further boosts this increase (Gibson et al 2014). However, Fortes and Whitham (2011) reported that eHSP70 in the saliva unchanged during and until 20 min after the exercise (60 min of treadmill running at 50−70 % VO 2max ) with hot environment (30°C).…”
Section: Introductionmentioning
confidence: 99%